2019
DOI: 10.1183/13993003.02429-2018
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen compared to air during exercise training in COPD with exercise-induced desaturation

Abstract: Almost half the patients referred to pulmonary rehabilitation with chronic obstructive pulmonary disease (COPD) desaturate during exercise. Although oxygen supplementation may ameliorate oxygen desaturation, the effects on outcomes of exercise training have not been rigorously evaluated. This study aimed to determine whether supplemental oxygen during exercise training was more effective than medical air in improving exercise capacity and health-related quality of life (HRQoL) in people with COPD.People with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 40 publications
3
57
1
6
Order By: Relevance
“…If there are clear signs of exercise-induced oxygendesaturation during the cardiopulmonary exercise test [55,56], the rehabilitation team may want to consider the use of oxygen supplementation during the whole-body exercise training, although its use has been questioned recently. Indeed, Alison and colleagues showed that a 10-week exercise training program was safe and effective in patients with COPD with mild exercise-induced O2-desaturation who were training with oxygen supplementation or room air supplementation [57].…”
Section: Different Modes Of Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…If there are clear signs of exercise-induced oxygendesaturation during the cardiopulmonary exercise test [55,56], the rehabilitation team may want to consider the use of oxygen supplementation during the whole-body exercise training, although its use has been questioned recently. Indeed, Alison and colleagues showed that a 10-week exercise training program was safe and effective in patients with COPD with mild exercise-induced O2-desaturation who were training with oxygen supplementation or room air supplementation [57].…”
Section: Different Modes Of Exercise Trainingmentioning
confidence: 99%
“…Also, Garrod et al [95] showed no benefits of training with supplemental oxygen compared to room air in patients with EID regarding exercise tolerance or health status. Very recently, a large doubleblinded RCT showed that supplemental oxygen used during an 8-week supervised exercise training program in normoxemic COPD patients with EID did not result in greater improvements in exercise capacity than did medical air [57]. This was a large prospective-blinded study, but the investigators did not evaluate the acute response to oxygen supplementation.…”
Section: Training Oxygen and Noninvasive Ventilatory Supportmentioning
confidence: 99%
“…Individualized oxygen titration trials may identify individuals with COPD who respond to oxygen supplementation during exercise testing . However, a recently published randomized controlled trial of 111 COPD patients, normoxaemic at rest but with exercise induced desaturation below 90% oxygen saturation (SpO 2 ), showed no difference in improvement in exercise capacity and quality of life with supplemental oxygen during exercise training compared to air …”
Section: Tools For Individualizing Exercise Programmesmentioning
confidence: 99%
“…In this issue of the European Respiratory Journal, ALISON et al [15] report on a double-blind randomised placebo-controlled trial that aimed to determine whether supplemental oxygen administered during exercise training was more effective than medical air in improving endurance exercise capacity, health-related quality of life, peak walking capacity, dyspnoea and physical activity levels in patients with COPD who desaturated during exercise (<90% during the 6-min walk test) but were normoxaemic at rest. Following random allocation to either oxygen or compressed air, both groups underwent an 8-week training programme with three supervised exercise sessions per week.…”
mentioning
confidence: 99%
“…ALISON et al [15] should be congratulated in rigorously conducting the largest study to date to examine the role of supplemental oxygen during exercise training in patients with COPD and EID. They provide convincing data that the majority of patients with COPD and EID safely benefit from exercise training without the need for supplemental oxygen.…”
mentioning
confidence: 99%